Focal Neurologic Deficits with Hypoglycemia and Diabetes - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
Focal neurologic deficits on 19 occasions in seven children with diabetes are reported from Children's Hospital, Winnipeg, Manitoba, Canada.